Arginase-negative mutants of Arabidopsis exhibit increased nitric oxide signaling in root development - Flores, Teresita (2008)
Mutation of either arginase structural gene (ARGAH1 or ARGAH2 encoding arginine [Arg] amidohydrolase-1 and -2, respectively) resulted in increased formation of lateral and adventitious roots in Arabidopsis (Arabidopsis thaliana) seedlings and increased nitric oxide (NO) accumulation and efflux, detected by the fluorogenic traps 3-amino,4-aminomethyl-2′,7′- difluorofluorescein diacetate and diamino-rhodamine-4M, respectively. Upon seedling exposure to the synthetic auxin naphthaleneacetic acid, NO accumulation was differentially enhanced in argah1-1 and argah2-1 compared with the wild type. In all genotypes, much 3-amino,4-aminomethyl-2′,7′- difluorofluorescein diacetate fluorescence originated from mitochondria. The arginases are both localized to the mitochondrial matrix and closely related. However, their expression levels and patterns differ: ARGAH1 encoded the minor activity, and ARGAH1-driven β-glucuronidase (GUS) was expressed throughout the seedling; the ARGAH2::GUS expression pattern was more localized. Naphthaleneacetic acid increased seedling lateral root numbers (total lateral roots per primary root) in the mutants to twice the number in the wild type, consistent with increased internal NO leading to enhanced auxin signaling in roots. In agreement, argah1-1 and argah2-1 showed increased expression of the auxin-responsive reporter DR5::GUS in root tips, emerging lateral roots, and hypocotyls. We propose that Arg, or an Arg derivative, is a potential NO source and that reduced arginase activity in the mutants results in greater conversion of Arg to NO, thereby potentiating auxin action in roots. This model is supported by supplemental Arg induction of adventitious roots and increased NO accumulation in argah1-1 and argah2-1 versus the wild type.